The low overpotential regime of acidic water oxidation part I: the importance of O2 detection. Issue 5 (31st March 2022) - Scott, Soren B.; Rao, Reshma R.; Moon, Choongman; Sørensen, Jakob E.; Kibsgaard, Jakob; Shao-Horn, Yang; Chorkendorff, Ib
Abstract : By measuring O2 with high sensitivity, we open a mechanistic window into water oxidation on RuO x in acid. Abstract : The high overpotential required for the oxygen evolution reaction (OER) represents a significant barrier for the production of closed-cycle renewable fuels and chemicals. Ruthenium dioxide is among the most active catalysts for OER in acid, but the activity at low overpotentials can be difficult to measure due to high capacitance. In this work, we use electrochemistry – mass spectrometry to obtain accurate OER activity measurements spanning six orders of magnitude on a model series of ruthenium-based catalysts in acidic electrolyte, quantifying electrocatalytic O2 production at potential as low as 1.30 VRHE . We show that the potential-dependent O2 production rate, i.e., the Tafel slope, exhibits three regimes, revealing a previously unobserved Tafel slope of 25 mV decade −1 below 1.4 VRHE . We fit the expanded activity data to a microkinetic model based on potential-dependent coverage of the surface intermediates from which the rate-determining step takes place. Our results demonstrate how the familiar quantities "onset potential" and "exchange current density" are influenced by the sensitivity of the detection method.